Adopting ISO 20022: Opportunities, Challenges, and Success Factors for Corporations in Payment Processing - João Constantino; Henrique São Mamede; Miguel Mira da Silva (Emerging Science Journal, 2024)
This research explores the adoption of ISO 20022, a standard that corporations can leverage to instruct payments to their partner financial institutions. Due to the complexity and case-specific variables involved, the adoption process may be complex and require significant effort from financial institutions and customers over an extended period. This research analyzes the opportunities and challenges for corporate users posed by ISO 20022 and identifies the success factors that must be considered during the adoption process. The research key findings indicate that an implementation approach incorporating flexibility, custom extensions, the use of a markup language for creating and managing messages, pilot testing, and user feedback can be an effective adoption model for ISO 20022. Design Science Research Methodology is employed in designing, building, and evaluating a solution proposal to develop a structured, customized, and flexible solution complying with the ever-changing requirements and landscape. This research contributes to the payment processing field by providing a comprehensive adoption model for ISO 20022 that considers critical factors and challenges. The proposed customized and flexible solution can assist corporations in successfully adopting ISO 20022 and contribute to creating a common language and model for payment data worldwide. The initiative's success depends on the effective adoption by all players, including corporations. Doi: 10.28991/ESJ-2024-08-04-010 Full Text: PDF